Talon′s cusp: Report of four unusual cases - Tulunoglu O; Cankala D; Ozdemir R (Wolters Kluwer Medknow Publications, 2007)
Talon cusp is a developmental dental anomaly thought to arise as a result of evagination on the surface of a tooth crown before calcification has occurred. The etiology remains unknown. The incidence is 0.04-10%. Any tooth may have a talon cusp but most of the cases involve maxillary lateral incisors, with some instances of bilateral involvement. The anomaly has been reported to be rare in the mandible. This article reports four cases of talon cusp. The first and the second cases describe bilateral involvement of talon cusp on palatal surfaces of maxillary primary centrals; in the third case talon tubercle occurs on palatal surfaces of both maxillary permanent lateral incisors and the maxillary left central incisor and in the last case a talon cusp in the lingual surface of mandibular permanent lateral incisor.